ECOLOGICAL AND ECONOMIC CONFLICTS: AGRICULTURAL USE OR CULTIVATION BIOMASS SECOND GENERATION - T. Trohlyuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
To negotiate the consequences of agricultural modernization as an example of nature Polissya areas in Ukraine. Studies addressing the conceptual foundations of ecological and economic conflict over agricultural use or cultivation of second generation biomass due to the transformation of land use during the economic reforms in the country. Proposed to solve it through socio-ecological-economic assessment of environmental audit procedure in the context of the strategy of "green" economy.